2018
DOI: 10.1002/jcu.22638
|View full text |Cite
|
Sign up to set email alerts
|

Implication of ultrasound contrast‐enhancement of carotid plaques in prevalence of acute coronary syndrome and occurrence of cardiovascular outcomes

Abstract: Purpose: Ultrasonographic contrast enhancement of carotid plaque (CECP) has been used to detect neovascularization of vasa vasorum and plaque. However, it is uncertain whether CECP can provide risk stratification of coronary artery disease (CAD). This study aimed to evaluate the relationship between CECP and manifestations of acute coronary syndrome (ACS) in established CAD patients and to explore the prognostic implication of CECP for cardiovascular (CV) clinical outcomes.Methods: A medical record review reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Some studies have suggested that intraplaque neovascularisation is significantly related to ischaemic stroke, that carotid plaque can independently predict significant and complex CAD, and that CEUS-assessed carotid IPN is a clinically useful tool in high-risk cardiac patients. 28,33 In the present study, we demonstrated that carotid intraplaque neovascularisation using CEUS can predict not only stroke recurrence but also cardiovascular events, which may represent a systematic burden of atherosclerotic disease.…”
Section: Discussionmentioning
confidence: 54%
“…Some studies have suggested that intraplaque neovascularisation is significantly related to ischaemic stroke, that carotid plaque can independently predict significant and complex CAD, and that CEUS-assessed carotid IPN is a clinically useful tool in high-risk cardiac patients. 28,33 In the present study, we demonstrated that carotid intraplaque neovascularisation using CEUS can predict not only stroke recurrence but also cardiovascular events, which may represent a systematic burden of atherosclerotic disease.…”
Section: Discussionmentioning
confidence: 54%
“…The sample size was calculated for a two-sample proportions test with study parameters: delta = –0.5080 (difference), p1 = 0.8050, p2 = 0.2970. 16 Power was set at 80%, confidence interval 95%, and α 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Doppler imaging was also performed and the following parameters were recorded: peak systolic velocity (PSV) of ICA and CCA, and carotid index was calculated using these values as PSV ICA/PSV CCA. 16 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations